Agricultural stakeholders’ priorities using Q method for initiation of an innovation platform in Nan, Thailand: 10.55131/jphd/2022/200215 - Jaitiang, Daranrat; Luther, Gregory C.; Tung, Shih-Jui; Takagi, Chifumi (Journal of Public Health and Development, 2022)
As a consequence of intensive maize mono-cropping practice on sloping lands in northern Thailand, Nan province, farmers face extremely low yields, soil erosion, and prolonged drought. Research and development efforts are needed to identify possible solutions, evaluate and scale them out to farmers. Consequently, an innovation platform has initiated a network of stakeholders, including farmers, government officers, researchers, and private sector actors, who meet regularly to coordinate the development of long-term solutions. Therefore, this study aims to identify which interests and goals are shared and which are conflicting among the various stakeholders involved in the Nan R4D platform, which was initiated as part of the Humidtropics project. Q methodology was employed, and 29 participants were selected from the R4D platform to conduct a Q-sort activity. The results showed that the two distinctive framings shared ways of thinking about research and development (R&D) and environmental issues. Additionally, participants’ interests and goals were diversifying agriculture, livestock promotion, growing vegetables, government aid, rubber plantation profitability, pesticide damage, deforestation, growing own food, and the possibility of growing maize sustainably. However, they disagreed on whether maize cultivation leads to food insecurity and high debt among farmers, and if planting fruit trees on sloping land is advisable. Ultimately, this study delivers agricultural stakeholders’ perspectives from the platform including recommendations on further potential policies for agricultural development in Nan.